Effect of Orem’s Self-Care Theory Combined with Active Pain Assessment on Pain, Stress and Psychological State of Children with Nephroblastoma Surgery - Tang, Yuanhui; Chen, Yaoyao; Li, Yanfang (Frontiers in Surgery, 2022)
Background With the development of medical technology and innovation of various surgical options, the survival time of children with nephroblastoma is significantly prolonged. However, postoperative pain and stress response have been plagued by children with nephroblastoma in the postoperative treatment. At present, there is still a lack of effective care programs. Materials and Methods We accessed our institutional database to retrospectively screen clinical data from all children with nephroblastoma who were surgically treated in our hospital between July 2020 and July 2021. Some children received routine care, while others received Orem-based self-care theory and active pain assessment. Results According to the inclusion and exclusion criteria, 150 children with nephroblastoma who underwent surgical treatment were included in this study. On the third day after surgery, the scores of pain control effect and satisfaction degree of pain education in the research group were higher than those in the control group, and the physical and daily life influence, emotion influence and pain experience in the study group were lower than those in the control group. The differences were statistically significant (P<0.001). There was no significant difference in C-SUPPH and ESCA scores between the two groups before nursing (P > 0.05). After nursing, the C-SUPPH and ESCA scores of the two groups were higher than those before nursing, and the C-SUPPH and ESCA scores of the research group were higher than those of the control group (P<0.05). Before nursing, the levels of ACTH, Cor and ANP between the two groups were not statistically significant (P > 0.05). The levels of ACTH, Cor and ANP in the two groups were lower than those before nursing 3d and 7d after nursing, and the index levels after 7d of nursing were lower than those after 3d of nursing. After nursing, the levels of ACTH. Conclusion Orem's self-care theory combined with active pain assessment can reduce pain in children undergoing nephroblastoma surgery, improve their stress response and psychological state, and improve their sleep quality, which is conducive to postoperative recovery and worthy of promotion.